Indices formal grammar of the Universal Decimal Classification - V. N. Beloozerov; A. V. Shapkin (Библиосфера)
The article proposes an algorithm for decoding and representation in natural language of the Universal Decimal Classifycation (UDC) complex class numbers. The algorithm is based on the formal definition of correct class numbers using a generative grammar, which sets the list of structures starting with simple table codes of UDC classes. Then separate integers, auxiliary and independent class numbers are sequentially attached to the codes with special symbols of relations of classes, which compose the complex class number. The algorithm expresses the values of the analyzed complex indices by descriptions (names and notes) of the table classes included in the structure of the analyzed string. The class descriptions are accompanied with the logical connectors based on the functions of the auxiliary characters. They provide the idea on connection of concepts denoted in the class number. The algorithm action is described evidently for the analysis of combined index 539.4.019: [535-15+537.8.029.6]. The proposed algorithm is applicable both to visualize the meaning of complex class numbers, and to ensure the completeness and accuracy of the documents retrieval by the UDC classes.